Styles of Curriculum Development. A Report of an International Conference (Monticello, Illinois, September 19-23, 1971) - Maclure, Stuart; Organisation for Economic Cooperation and Development, Paris (France). Centre for Educational Research and Innovation; Illinois Univ., Urbana ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
Thirty-nine people from 10 OECD member countries participated at this conference aimed at setting the value-loaded questions of curriculum development in an international context. The conference looked at the relationship between development styles for development enterprises as a whole and the developmental pattern of individual projects. Attention was concentrated on how curriculum developments are defined and by whom, in what terms they are formulated, and how activities are generated in response to these needs and purposes. Much of the discussion centered around (1) the contrast between centralized and decentralized systems; (2) the impact of curriculum development on the role of the teacher; and (3) the relationship between the center and the periphery -- referring to central government curriculum department and schools. This document synthesizes the substance of four discussion groups. (Author/MLF)
Availability: OECD Publications Center, Suite 1207, 1750 Pennsylvania Ave., N.W. Washington, D.C. 20006 ($2.00).
Sponsoring Agency: National Science Foundation, Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Concept Formation; Conference Reports; Consolidated Schools; Curriculum Development; Decentralization; Educational Change; Educational Innovation; Educational Philosophy; International Organizations; Models; School Organization; Social Change; Values